«Sobre ti paso extraña». María Zambrano, una poética de la catástrofe - Laurence Breysse-Chanet (Catalonia)
At the very place of catastrophe, a new birth occurs. The life and work of the Andalusian philosopher María Zambrano, who lived in exile from the fall of Barcelona in January 1939 to 1984, might serve to support this premise, provided that profound suffering can lay ground for a well-founded certainty. Yet her writings never cease to give substance to this assertion, as will be demonstrated through the study of a corpus of texts written between late 1938 and early 1939, collected under the title « Escritos autobiográficos. Delirios. Poemas ». Drawing on these pages, we will see how María united her fate to poetry through « poetic reason », which was notably embodied in the figure of her Antigone, a body of reconciliation, achieved through memory and love.